PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR BERKREASI GERAK TARI SEDERHANA PADA PESERTA DIDIKKELAS X KECANTIKAN W1 SMK N 3 DENPASAR - I Made Sujana; I Gusti Agung Ayu Tirta Triratna (CV. ADIBA ASIHA AMIRA, 2023)
Classroom Action Research (PTK) class X Beauty W1 at SMK N 3 Denpasar aims to improve the learning outcomes of creating simple dance movements with the application of the peer tutor method. The data collection techniques used are observation of the implementation of the action and the results achieved, and the action test of creating simple dance movements. While the data analysis technique used is qualitative descriptive analysis of the entire process of implementing dance learning in class X Beauty W1 SMK N 3 Denpasar using the peer tutor method and quantitative to test the results of students' action tests by comparing the average value of the completeness of learning outcomes. The results showed that the average learning outcomes of creating simple dance movements in class X Beauty W1 increased from cycle I to cycle II, which can be seen from the increase in the average obtained from the action test results. The average class score in cycle I was 79.64, the highest score was 86 and the lowest score was 68. The number of students who did not complete was 2 people (5.12%) while those who scored only at the KKM limit were 8 students (20.51%) and those who scored above KKM were 29 children (74.32%), while in cycle II the average class score was 82.53, the highest score was 87 and the lowest score was 78 and the number of students who scored above KKM was 39 children (100%).